Accelerating savanna degradation threatens the Maasai Mara socio-ecological system. (January 2020) - Li, Wang; Buitenwerf, Robert; Munk, Michael; Amoke, Irene; Bøcher, Peder Klith; Svenning, Jens-Christian
Highlights: Massive and accelerating degradation and fragmentation of natural vegetation with the expansion of bare ground was observed in the unprotected land in Mara ecosystem. Directional change was minimal in the fully protected national reserve. Vegetation resistance to drought was lowest on unprotected land, intermediate under community-based conservation and highest under full protection. The Mara ecosystem is heavily threatened, but conservation management can counteract negative trends. Semi-protected community-based land-sharing conservation offers clear, partial buffering against degradation. Abstract: Savanna megafauna have become scarce outside of protected areas in Africa, largely because of land conversion for farming (smallholders and agribusiness) and expansion of settlements and other infrastructure. Intensification also isolates protected areas, even affecting natural processes within reserve boundaries. Here, we used satellite imagery from the past 32 years in the iconic Maasai Mara ecosystem to assess the capacity of different land tenures to prevent degradation. We compare unprotected land with two types of conservation management: fully protected land without livestock (land sparing) and semi-protected community-based conservation – protected land with regulated livestock densities (land sharing). On unprotected land (61% of the area), we detected massive and accelerating degradation and fragmentation of natural vegetation, with large losses of woodland (62%) and grassland (56%), resulting in the expansion of bare ground. In contrast, directional change was minimal in both types of protected areas. Vegetation resistance to drought was lowest on unprotected land, intermediate under community-based conservation and highest under full protection. Our results show that the Mara ecosystem is under heavy pressure, but that conservation management counteracts negative trends. Importantly, semi-protected community-based land-sharing conservation offers clear, partial buffering against degradation.